An 8.07% efficient fiber dye-sensitized solar cell based on a TiO2 micron-core array and multilayer structure photoanode. (January 2015) - Liu, Guicheng; Peng, Ming; Song, Weixing; Wang, Hui; Zou, Dechun
Abstract: Ti/TiO2 micron-cone array (TMCA) prepared through a synergy of chemical and electrochemical reactions was used as the frame and electron transfer channel for the photoanode of a fiber dye-sensitized solar cell (FDSSC). A TiO2 multilayer structure composed of compact, light scattering, and porous layers was introduced into the fiber photoanode for the first time based on the TMCA. The novel fiber photoelectric device attained a photoelectric conversion efficiency of 8.07%, the highest value for FDSSCs with a Pt wire counter electrode to date, and a good flexibility. Graphical abstract: Ti/TiO2 micron-cone array was used as the frame and electron transfer channel for a fiber dye-sensitized solar cell. A high photoelectric efficiency of up to 8.07% was achieved. Highlights: A Ti/TiO2 micron-cone array electrode was prepared as a novel anode substrate through a synergy of chemical and electrochemical reactions. A TiO2 multilayer structure composed of compact, light scattering, and porous layers was introduced into the fiber photoanode. The novel fiber photoelectric device attained a photoelectric conversion efficiency of 8.07% and a good flexibility.